1992
DOI: 10.1002/1097-0142(19920701)70:1<28::aid-cncr2820700105>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resections for colorectal metastases in the Netherlands a multiinstitutional 10-year study

Abstract: Background and Methods. The records of 118 patients who had hepatic resections for colorectal liver metastases were analyzed retrospectively. Results. The patient group, from 15 institutions in The Netherlands, was found to have a 5‐year actuarial survival rate of 21% and a 5‐year actuarial disease‐free survival rate of 19%. The postoperative mortality rate was 7.6%. In the remaining group, the morbidity rate was 34.7%. A number of factors were examined that were reported to be of prospective significance in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…Eighteen of these were single publications (Savage and Malt, 1992;Sugihara et al, 1993; Donato et al, 1994; Doci et al, 1995; Fernandez-Trigo et al, 1995; Fuhrman et al, 1995; Beckurts et al, 1997;Rees et al, 1997; Cady et al, 1998; Ohlsson et al, 1998;Riesener et al, 1998; Bradley et al, 1999; Harmon et al, 1999; Harms et al, 1999; Kemeny et al, 1999a; Bolton and Fuhrman, 2000; Okano et al, 2000; Moroz et al, 2002) and in a further 12 cases the data was obtained from multiple publications (Hughes et al, 1988(Hughes et al, , 1989 Hohenberger et al, 1990 Hohenberger et al, , 1994Scheele et al, 1990Scheele et al, , 1991Scheele et al, , 1995Scheele et al, , 1996Steele Jr et al, 1991Rosen et al, 1992; Gayowski et al, 1994;Stangl et al, 1994; Fong et al, 1995 Fong et al, , 1997 Fong et al, , 1999 Leslie et al, 1995; Jamison et al, 1996 Jamison et al, , 1997 Jenkins et al, 1997; Bakalakos et al, 1998a, b; Iwatsuki et al, 1999; Minagawa et al, 1999; Ambiru et al, 1999a; Kemeny et al, 1999b, c; Brand et al, 2000; DeMatteo et al, 2000; Minagawa et al, 2000). In addition, data on 30-day mortality and morbidity were included from a further nine studies (one with two publications) in which survival data was excluded owing to insufficient or unclear follow up (Minton and Abou-Issa, 1990; Fegiz et al, 1991; Nordlinger et al, 1992;van Ooijen et al, 1992;Wade et al, 1996; Lorenz et al, 1997 Lorenz et al, , 1998; Nadig et al, 1997; Taylor Just two studies included all patients presenting with colorectal liver metastases (Scheele et al, 1990(Scheele et al, , 1991(Scheele et al, , 1995(Scheele et al, , 1996Stangl et al, 1994; Harms et al, 1999) and only three studies presented data on all patients undergoing surgery (radical, nonradical and laparotomy) (Steele Jr et al, 1991 Fuhrman et al, 1995; Bakalakos et al, 1998a). The majority (27) of studies presented data on resected patients, but while some studies distinguished between R0 resections (no residual disease, histologically clear margins), R1 (histologically involved margins) and R2 resections (macroscopic residual disease), in many this was unclear.…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen of these were single publications (Savage and Malt, 1992;Sugihara et al, 1993; Donato et al, 1994; Doci et al, 1995; Fernandez-Trigo et al, 1995; Fuhrman et al, 1995; Beckurts et al, 1997;Rees et al, 1997; Cady et al, 1998; Ohlsson et al, 1998;Riesener et al, 1998; Bradley et al, 1999; Harmon et al, 1999; Harms et al, 1999; Kemeny et al, 1999a; Bolton and Fuhrman, 2000; Okano et al, 2000; Moroz et al, 2002) and in a further 12 cases the data was obtained from multiple publications (Hughes et al, 1988(Hughes et al, , 1989 Hohenberger et al, 1990 Hohenberger et al, , 1994Scheele et al, 1990Scheele et al, , 1991Scheele et al, , 1995Scheele et al, , 1996Steele Jr et al, 1991Rosen et al, 1992; Gayowski et al, 1994;Stangl et al, 1994; Fong et al, 1995 Fong et al, , 1997 Fong et al, , 1999 Leslie et al, 1995; Jamison et al, 1996 Jamison et al, , 1997 Jenkins et al, 1997; Bakalakos et al, 1998a, b; Iwatsuki et al, 1999; Minagawa et al, 1999; Ambiru et al, 1999a; Kemeny et al, 1999b, c; Brand et al, 2000; DeMatteo et al, 2000; Minagawa et al, 2000). In addition, data on 30-day mortality and morbidity were included from a further nine studies (one with two publications) in which survival data was excluded owing to insufficient or unclear follow up (Minton and Abou-Issa, 1990; Fegiz et al, 1991; Nordlinger et al, 1992;van Ooijen et al, 1992;Wade et al, 1996; Lorenz et al, 1997 Lorenz et al, , 1998; Nadig et al, 1997; Taylor Just two studies included all patients presenting with colorectal liver metastases (Scheele et al, 1990(Scheele et al, , 1991(Scheele et al, , 1995(Scheele et al, , 1996Stangl et al, 1994; Harms et al, 1999) and only three studies presented data on all patients undergoing surgery (radical, nonradical and laparotomy) (Steele Jr et al, 1991 Fuhrman et al, 1995; Bakalakos et al, 1998a). The majority (27) of studies presented data on resected patients, but while some studies distinguished between R0 resections (no residual disease, histologically clear margins), R1 (histologically involved margins) and R2 resections (macroscopic residual disease), in many this was unclear.…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…However, some studies reported fatal complications only (van Ooijen et al, 1992;Scheele et al, 1996; Lorenz et al, 1998; Bolton and Fuhrman, 2000; Moroz et al, 2002), length of hospital stay only (Hohenberger et al, 1994; Fuhrman et al, 1995), blood transfusions only (Jamison et al, 1997) or simply reported the number of patients with nonspecified complications (van Ooijen et al, 1992; Fernandez-Trigo et al, 1995;Scheele et al, 1996; Jenkins et al, 1997;Taylor et al, 1997; Bakalakos et al, 1998a; Fong et al, 1999; Figueras et al, 2001).…”
Section: Postoperative Morbiditymentioning
confidence: 99%
“…For these studies, a weighted mean was calculated using the number of patients in each sub-category and the corresponding percentage survival, to compute percentage survival for the whole <1 cm negative margin sub-group. Some studies [3,[5][6][7] categorized negative margins as "≤1 cm and >1 cm" while others [4,[8][9][10][11][12][13][14] used "<1 cm and ≥1 cm" for negative margins. For the purpose of meta-analysis ≤1 cm and <1 cm were treated as "<1 cm" and > 1 cm or ≥1 cm were treated as "≥1 cm".…”
Section: Data Extraction and Definitionsmentioning
confidence: 99%
“…Hepatic resection remains a well accepted modality in the treatment of patients with colorectal liver metastases (CRLM) with 5 year overall survival (OS) ranging from 37 % to 58 % [1][2][3][4] and 5 year disease free survival (DFS) ranging from 11 % to 50 % [3,[5][6][7][8][9][10][11][12][13][14]. Recurrence of the disease after resection still remains a challenge and adversely affects the long term outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation